Ohmic heating curing of carbon fiber/carbon nanofiber synergistically strengthening cement-based composites as repair/reinforcement materials used in ultra-low temperature environment. (October 2019) - Liu, Yushi; Wang, Mingzhi; Tian, Weichen; Qi, Beimeng; Lei, Zhongyao; Wang, Wei
Abstract: The repair/reinforcement of construction structures have been a challenge due to hydration termination of cement-based materials in an ultra-low temperature environment. This work presents a Carbon Fiber (CF)/Carbon Nanofiber (CNF) synergistically strengthening cement-based composite (CM-CF/CNF) as a repair/reinforcement material, in which ohmic heating curing of CM-CF/CNF is utilized to enhance structural strength at ultra-low temperature. Conductive paths in cement-based composite are formed with added CFs, which also improves mechanical properties, and the stabilization of the conductive network constructed by CFs is enhanced by incorporation of CNFs. A numerical model is established to evaluate CFs bridging behavior, and the role of CNFs in the stabilization of conductive network is numerically discussed based on permeation theory. A continuous maintenance of temperature is achieved with CM-CF/CNF cured by ohmic heating at −20 °C, and the cured sample shows superior 2-day compressive and flexural strengths of 49.2 MPa and 11.5 MPa, respectively.